Construction of a high-performance air-breathing cathode using platinum catalyst supported by carbon black and carbon nanotubes. (8th June 2016) - Xiong, Zi'ang; Liao, Shijun; Hou, Sanying; Zou, Haobin; Dang, Dai; Tian, Xinlong; Nan, Haoxiong; Shu, Ting; Du, Li
Abstract: It is well recognized that pore structure and the hydrophilicity/hydrophobicity balance are key factors for the cathodes of air-breathing proton exchange membrane fuel cells (AB-PEMFCs). In this work, we attempted to adjust the pore structure and hydrophilicity of an air-breathing cathode by using two types of catalysts, Pt/C and Pt/CNT, to prepare the catalyst layer for the air-breathing cathode instead of using a single catalyst. An MEA with the dual-catalyst cathode exhibited significantly improved single-cell performance, which was affected by the ratio of Pt/C to Pt/CNT. Our optimized MEA, which had a ratio of 54:46 in the cathode catalyst layer, achieved a current density of up to 290 mA cm −2 at 0.6 V, which was 14% higher than that of a MEA without Pt/CNT. The Pt/CNT in the catalyst layer played the key role in the overall performance of the AB-PEMFC. We propose that the CNT improved charge transfer and enabled better electrical conductivity than carbon black. In addition, the tubular structure of Pt/CNT made the catalyst layer more porous and permeable to gas. Furthermore, the addition of Pt/CNT may have changed the cathode's hydrophilicity/hydrophobicity balance, giving the cathode better water balance and consequently yielding better performance. Graphical abstract: A high performance air-breathing cathode for air-breathing PEMFCs is prepared by using the mixture of Pt/C and Pt/CNTs as cathode catalysts. The significantly enhanced performance has been achieved by the PEMFC with the cathode. Highlights: A air-breathing cathode was prepared with mixture of Pt/CNT and Pt/C as catalyst. The performance of air-breathing PEMFC with the cathode is enhanced significantly. The porosity and water management are improved through inducing Pt/CNTs catalyst.